Association between CETP gene polymorphism, insulin resistance and risk of diabetes mellitus in patients with vascular disease. Issue 2 (October 2015) - Koopal, Charlotte; van der Graaf, Yolanda; Asselbergs, Folkert W.; Westerink, Jan; Visseren, Frank L.J.; ,
Abstract: Introduction: Genetic inhibition of Cholesteryl Ester Transfer Protein (CETP) might be associated with insulin resistance and incident type 2 diabetes mellitus (T2DM). This study investigated the relation between a genetic variant in the CETP gene and measures of insulin resistance and incident T2DM in patients with manifest cardiovascular disease (CVD). Furthermore the effect on risk of recurrent cardiovascular events was investigated. Methods: SMART is a prospective cohort study performed in 5601 patients with clinically manifest CVD. We selected a variant (rs3764261) associated with reduced CETP activity and increased levels of HDL cholesterol (HDL-C). Patients were divided in three groups: 2640 wild type patients (GG), 2420 heterozygotes for rs3764261 (GT) and 541 homozygotes for rs3764261 (TT). Regression analyses were performed using an additive model. Results: The study population consisted of 4656 patients without T2DM and 945 patients with T2DM at baseline. Presence of rs3764261 was associated with increased HDL-C in patients without T2DM (β 0.106, 95%CI 0.083–0.128) and with T2DM (β 0.043, 95%CI 0.007–0.078). During a median follow up of 7.2 years (IQR 4.7–10.2) 427 incident T2DM occurred. Presence of rs3764261 was not related to incident T2DM (HR 0.96, 95%CI 0.83–1.11) in patients without T2DM at baseline. Furthermore, presence of rs3764261 was not related to insulin resistance (glucose, insulin, HOMA-IR, HbA1c) or recurrent CVD (HR 0.92, 95%CI 0.84–1.02). Conclusion: Presence of CETP SNP rs3764261 is not associated with insulin resistance and incident T2DM in patients with clinically manifest vascular disease. Furthermore, no effect of rs3764261 on the risk of recurrent CVD was observed. Highlights: Cohort study in 5601 patients with clinically manifest vascular disease. CETP gene polymorphism is not associated with risk of diabetes mellitus. Insulin resistance is not affected by CETP gene polymorphism.